Comparison of two commonly used reference materials for exercise bicycle tests with a Swedish clinical database of patients with normal outcome. (31st October 2013) - Brudin, L.; Jorfeldt, L.; Pahlm, O.
Summary Background Reference values for working capacity, blood pressure, heart rate, perceived exertion, etc. during bicycle exercise tests have been sought after for many years. This is because earlier commonly used reference values for physical work capacity have been either too low or too high when compared to the clinical experience of several Swedish departments of clinical physiology. The aim of the study was to compare two commonly used reference materials with normal outcomes from a clinical database. Methods Data from a clinical database of standardized exercise tests in Kalmar, Sweden, between 2004 and 2012, and having been judged as normal, were divided into 5‐year categories of 5–10 to 75–80 years of age covering people from 7 to 80 years of age. Results Maximal working capacity (Wmax), maximal heart rate, maximal systolic blood pressure and maximal perceived exertion are presented for each of the 15 age categories. Regression equations are also presented for each sex with age and height as independent predictors. Quantitative comparisons of Wmax are calculated for the three materials and possible explanations discussed. Conclusions Values of Wmax lie between the two reference materials most commonly used in Sweden. In addition, the present material covers subjects aged 7–19 years.